Pengembangan Media Pembelajaran Video Animasi Berbasis Discovery Learning SMP untuk Membangun Minat Belajar Siswa - Fitri Herlinawati; Widayanti Widayanti; Effendi Effendi (Pendidikan Fisika Universitas Nurul Huda, 2022)
This study aims to (1) develop animated video learning media in Sciences (IPA) subject matter on global warming, (2) find out the validator's response to discovery learning based video animation learning media on global warming material in Junior High Schools (SMP) class VII , (3) knowing the feasibility of discovery learning based animation video learning media. This research is an R&D research with the design of the DDD-E development model which includes Decide, Design, Develop, Evaluate which is carried out until the fourth stage. The data collection instrument used in this study was a validation sheet given to 3 material expert validators and 3 media expert validators. The type of data generated is quantitative data which is analyzed with the guidelines of the assessment category criteria to determine product quality. The results of the analysis obtained in this study were: (1) video animation learning media, (2) discovery learning based animation video learning media the final product that was produced met the validity criteria with an average score from the assessment of material experts, 0.91% and media experts 0.88% in the high validity category, (3) Product feasibility in discovery learning-based video animation learning media with a field trial percentage of 88.09% in the very high category where these results show that animated videos can foster student learning interest